(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
SOMMARIO: 1. Premessa - 2. L’adozione delle misure di contenimento tra uguale tempestività e diversità procedurale - 3. Sostanziale uniformità dei provvedimenti - 4. Reazioni diverse alle misure restrittive da parte dei gruppi religiosi e delle associazioni filosofiche non confessionali - 5. Osservazioni conclusive. Freedom of worship in the time of the SARS-CoV-2 pandemic. Standard of protection in Italy, France and Belgium ABSTRACT: the contribution intends to analyze, through a comparative key, the operational strategies adopted by the Belgian, French and Italian governments and the responses of religious groups affected by the restrictive measures of freedom of worship. The choice of these three States - Belgium, France, Italy - is motivated by the specificity of their models of relations between the State and the religious phenomenon; it allows a perspective view able to offer constructive food for thought. The analysis does not claim to be exhaustive, since the pandemic situation is, unfortunately, still evolving, which makes crisis management policies susceptible to sudden changes and adaptations.